Biogas production potential from kraft pulp mill sludge - Lopes, Alice do Carmo Precci (2017)
The kraft pulping process is energy intensive. Although the mill generates part of its own energy by burning the black liquor in the recovery boiler and wooden biomass in the biomass boiler, it still relies on additional electricity and fossil fuel sources. Due to an energy price increase, the pulp industry has been driven to optimize its energy efficiency and self-sufficiency. One attractive industrial opportunity is to produce biogas from sludge using the anaerobic digestion technology. Thus, the main objective of this dissertation was to evaluate the potential of biogas production from bleached kraft pulp mill primary and secondary sludges. The dissertation was structured in 5 Chapters written as scientific papers. Chapter 1 presented a literature review about kraft pulp mills, biogas production, and legislations related to the implantation of biodigesters. It was concluded that there are still very few studies related to the anaerobic digestion of kraft pulp mill sludges. Additionally, although Brazil has great potential for biogas production, the country still faces barriers related to political incentives. Chapter 2 aimed at (i) identifying the best substrate to inoculum ratio (2/1, 1/1, and 0.4 g VS substrate /g VS inoculum ); (ii) identifying the best inoculum type (UASB sludge and UASB sludge + cow dung); and (iii) estimating the potential of substituting the electricity demand of the mill’s effluent treatment plant (ETP) aeration system. The substrates used consisted of primary (PS) and secondary (SS) sludges, and the mixture (MIX) between PS and SS. The results showed that the SS presented the highest methane production, with an optimal ratio of 1 g VS substrate /g VS inoculum using UASB sludge as inoculum. Cow dung increased the methane production of the PS for S/I = 1/1, but pre-treatment of PS should be tested to increase the substrate biodegradability. Finally, the methane yield led to a potential substitution of 23% of the ETP electricity demand. Chapter 3 aimed to (i) estimate potential biogas production under thermophilic conditions for the same substrates; (ii) calibrate the anaerobic digestion model developed by Rajendran et al. (2014); and (iii) simulate the best sludge composition and the influence of nitrogen addition on anaerobic digestion system. It was found that the (i) the maximum methane yield was achieved with theix secondary sludge at 30 days (46.9 NmL CH4/g VS); (ii) the applied anaerobic digestion model was applicable for the kraft pulp mill sludge after minor adjustments; (iii) optimal sludge composition was found to be 21.62% carbohydrates, 61.67% lipids and 16.72% proteins. The addition of nitrogen increased the methane yield for PS and MIX, but decreased it for SS. Chapters 4 and 5 were the result of work developed by bachelor exchange students as part of the Living Lab Biobased Brazil Program. Chapter 4 aimed to adjust the Rajendran et al. (2014) model for mesophilic conditions and simulate biogas use in the form of electricity and heat. From the simulation, a potential heat production of 88 GJ/d and electric power of 148 kW was found. From Chapter 4, possibilities for improving the Rajendran et al. (2014) model were proposed. Finally, Chapter 5 aimed at giving an insight into the possible alternatives for managing the anaerobically digested kraft pulp mill sludge using a simplified Multi- Criteria Decision Analysis tool. From the analyzed alternatives (landfill, land application, composting, incineration, pyrolysis/gasification and algae production), composting appeared to be the most suitable alternative.